2021
DOI: 10.5858/arpa.2020-0315-oa
|View full text |Cite
|
Sign up to set email alerts
|

Enterochromaffin-like Cell Hyperplasia–Associated Gastric Neuroendocrine Tumors May Arise in the Setting of Proton Pump Inhibitor Use

Abstract: Context.— Hypergastrinemia states such as achlorhydria from gastric mucosal atrophy or a gastrin-producing tumor in humans have been associated with the development of enterochromaffin-like (ECL) cell hyperplasia and gastric neuroendocrine tumors (GNETs). Whether drugs that can elevate serum gastrin levels, such as proton pump inhibitors (PPIs), can produce the same tissue effect is not known and there is no concrete evidence linking the use of PPIs to GNETs outside animal models and case rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…It is well known that gastritis caused by H. pylori infection is an important factor leading to gastric cancer. Chronic H. pylori infection may induce gastric neuroendocrine tumours under the condition of hypergastrinemia ( Rais et al, 2022 ). Subgroup analysis showed that the use of PPI and the risk of gastric cancer increased nearly threefold after eradication of potential confounders of H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that gastritis caused by H. pylori infection is an important factor leading to gastric cancer. Chronic H. pylori infection may induce gastric neuroendocrine tumours under the condition of hypergastrinemia ( Rais et al, 2022 ). Subgroup analysis showed that the use of PPI and the risk of gastric cancer increased nearly threefold after eradication of potential confounders of H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that nobody has explained why the inflammation has a selectively trophic effect on ECL cells. With the increasing acceptance of proton pump inhibitor-induced gastric NETs, we ( 82 ) and others ( 83 ) have come up with a new way to classify these tumors. We suggested that group 1 should comprise gastric NETs due to hypergastrinemia and that group 2 should comprise those not showing hypergastrinemia ( 82 ), whereas Rais et al.…”
Section: Gastric Cancermentioning
confidence: 99%
“…Clinical meta-analyses have demonstrated that long-term PPI use can exacerbate various conditions, including gastric cancer [ 11 ]. It can lead to hypergastrinemia due to potent gastric acid suppression, triggering intestinal chromaffin cell proliferation [ 12 ]. Prolonged PPI use, particularly in the presence of H. pylori infection, has been linked to the development of gastric cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can lead to hypergastrinemia due to potent gastric acid suppression, triggering intestinal chromaffin cell proliferation [ 12 ]. Prolonged PPI use, particularly in the presence of H. pylori infection, has been linked to the development of gastric cancer [ 12 ]. Consequently, exploring alternatives to mitigate these treatment side effects becomes imperative.…”
Section: Introductionmentioning
confidence: 99%